Arresting inflammation: contributions of plasma membrane and endosomal signalling to neuropeptide-driven inflammatory disease. (29th January 2013) - Cattaruzza, Fiore; Poole, Daniel P.; Bunnett, Nigel W.
Abstract : GPCR (G-protein-coupled receptor) signalling at the plasma membrane is under tight control. In the case of neuropeptides such as SP (substance P), plasma membrane signalling is regulated by cell-surface endopeptidases (e.g. neprilysin) that degrade extracellular neuropeptides, and receptor interaction with β-arrestins, which uncouple receptors from heterotrimeric G-proteins and mediate receptor endocytosis. By recruiting GPCRs, kinases and phosphatases to endocytosed GPCRs, β-arrestins assemble signalosomes that can mediate a second wave of signalling by internalized receptors. Endosomal peptidases, such as ECE-1 (endothelin-converting enzyme-1), can degrade SP in acidified endosomes, which destabilizes signalosomes and allows receptors, freed from β-arrestins, to recycle and resensitize. By disassembling signalosomes, ECE-1 terminates β-arrestin-mediated endosomal signalling. These mechanisms have been studied in model cell systems, and the relative importance of plasma membrane and endosomal signalling to complex pathophysiological processes, such as inflammation, pain and proliferation, is unclear. However, deletion or inhibition of metalloendopeptidases that control neuropeptide signalling at the plasma membrane and in endosomes has marked effects on inflammation. Neprilysin deletion exacerbates inflammation because of diminished degradation of pro-inflammatory SP. Conversely, inhibition of ECE-1 attenuates inflammation by preventing receptor recycling/resensitization, which is required for sustained pro-inflammatory signals from the plasma membrane. β-Arrestin deletion also affects inflammation because of the involvement of β-arrestins in pro-inflammatory signalling and migration of inflammatory cells. Knowledge of GPCR signalling in specific subcellular locations provides insights into pathophysiological processes, and can provide new opportunities for therapy. Selective targeting of β-arrestin-mediated endosomal signalling or of mechanisms of receptor recycling/resensitization may offer more effective and selective treatments than global targeting of cell-surface signalling.